Perverse Interfaces: Gaping, Drifting, and Rippling as Ontological Styles in Computer Games - Konstantin A. Ocheretyany (Галактика медиа: журнал медиа исследований)
We use interfaces to disconnect from the situation around us, from the persistent experience of the outside world, from our neighbors. It is this ability of interfaces to legitimize “absence” that is usually overlooked in their analysis, as the emphasis is on concentration, management, and control. In reality, interfaces are not so much pragmatic and utilitarian as experimental and perverse. In this article, the concept of ontological styles is introduced, and using the example of computer games, it shows how interfaces work with such ontological styles as yawning, drift, and ripple. Interfaces that define the conditions of presence in digital reality are usually thought of based on a bodily schema and possible behavioral scenarios; this article attempts to think of interfaces based on moments of “not-Self”, (not)possible worlds and alternative ways of existence in them.